Dielectric Properties and Impedance Spectroscopy of MnCO3‐Modified (Ba0.85Ca0.15)(Zr0.1Ti0.9)O3 Lead‐Free Ceramics. Issue 5 (3rd February 2015) - Wang, Xiaofang; Liang, Pengfei; Chao, Xiaolian; Yang, Zupei
Abstract : A MnCO3 ‐modified (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9 )O3 system was synthesized by solid‐state reaction method. The phase structure, microstructure, electrical properties, and complex impedance were investigated in detail. The addition of small amount of MnCO3 was quite effective to lower the sintering temperature. XRD analysis showed that the single perovskite phase was achieved in all compositions. XPS results demonstrated that the Mn ions were present in the mixed valence form of +2 and +4. The existence of Mn 2+ ions gave rise to an increase in oxygen vacancies and suppressed the piezoelectric and ferroelectric properties of samples. The diffusive phase transition was enhanced while the Curie temperature was remained in the vicinity of 90°C. In addition, according to the impedance analysis, it was concluded that the dielectric relaxation behavior was non‐Debye type and the movements of singly ionized oxygen vacancies played an important role in the conduction behavior at higher temperatures.